Information Voyeurism: Social Impact of Physically Large Displays on Information Privacy - Tan, Desney; Czerwinski, Mary (CHI 2003, 2003)
A common observation when working on physically large displays, such as wall-sized projection, is that a certain amount of information privacy is lost. A common explanation for this loss in privacy is the higher legibility of information presented on large displays. In this paper, we present a novel paradigm for measuring whether or not a user has read certain content. We show that, even with constant visual angles and legibility, visitors are still more likely to glance over a user’s shoulder to read information on a large wall-projected display than on a smaller traditional desktop monitor. We assert that, in addition to legibility, there are more subtle social factors that may contribute to the loss of privacy on physically large displays. Implementing hardware and software ideas for mitigating this loss of privacy remains future research.